Early Cretaceous continental delamination in the Yangtze Block: Evidence from high-Mg adakitic intrusions along the Tanlu fault, central Eastern China. (1st September 2016) - Jia, Liqiong; Mo, Xuanxue; Santosh, M.; Yang, Zhusen; Yang, Dan; Dong, Guochen; Wang, Liang; Wang, Xinchun; Wu, Xuan
Graphical abstract: Cartoons showing the geodynamic processes that generated the Cretaceous magmatic rocks including high Mg adakitic intrusion via partial melting of thickened and delaminated lower crust. Highlights: Zircon 206 Pb/ 238 U ages of high Mg adakitic rocks show emplacement during 120–129 Ma. Whole-rock Nd, Sr and Pb isotopes and zircon Lu-Hf data indicate magma derivation from continental crust. Partial melting of over-thickened basaltic lower crust following delamination. Abstract: Early Cretaceous high-Mg adakitic rocks from central Eastern China provide important insights into the thinning mechanism of the over-thickened lithosphere in the Yangtze Block (YB) as well as the North China Block (NCB). The Tanlu fault (TLF), located between the North China and Yangtze Blocks, and has been considered as a prominent pathway of magmas and fluids that resulted in lithosphere thinning of the YB during the Mesozoic–Cenozoic. Here we report the petrology, whole-rock geochemistry, zircon U–Pb geochronology, in situ Hf isotopes, and whole-rock Sr–Nd–Pb isotopes of four high-Mg adakitic intrusions along the TLF in northeastern Langdai. These adakitic intrusions consist of monzodiorite, quartz monzonite porphyry, and quartz monzodiorite. Zircon LA-MC-ICPMS analyses of five samples yield weighted mean 206 Pb/ 238 U ages of 127.58 ± 0.80, 126.90 ± 0.81, 120.71 ± 0.64, 122.75 ± 0.57, and 129.2 ± 1.1 Ma, indicating their emplacement during the Early Cretaceous. The intrusions have intermediate SiO2 (53.18–65.48 wt%) and high potassium (K2 O = 3.07–3.95 wt%; Na2 O/K2 O = 1.02–1.26) and are classified as shoshonitic to high-K calc-alkaline series. They are characterized by high MgO (1.80–7.35 wt%), Mg # (50–65), Sr (591–1183 ppm), Ni (20.3–143.0 ppm), and Cr (51.40–390.0 ppm) contents, high (La/Yb)N (11.60–28.33) and Sr/Y (27.9–113.5) ratios, and low Y (7.79–22.4 ppm) and Yb (0.60–2.01 ppm) contents, comparable with high-Mg adakites. The samples are enriched in light rare earth elements but depleted in heavy rare earth elements and high field strength elements with slightly negative to positive Eu anomalies ( δ Eu  = 0.81–1.30), resembling the features of high-Mg adakitic rocks. Their whole-rock ε Nd( t )  = −16.2 to −15.0, initial ( 87 Sr/ 86 Sr)i  = 0.7060–0.7074, low radiogenic Pb ( 206 Pb/ 204 Pb( t ) = 16.208–16.509, 207 Pb/ 204 Pb( t ) = 15.331–15.410, and 208 Pb/ 204 Pb( t ) = 36.551–36.992), and zircon ε Hf( t )  = −36.6 to −16.6 suggest magma derivation from a continental crustal source. The geochemical and isotopic features, in combination with existing geological data, suggest that the intrusions are high-Mg adakites and, by comparison with contemporaneous intrusions in Eastern China, were likely to have been formed by partial melting of over-thickened basaltic lower crust following the delamination of eclogitic lithosphere during the Late Jurassic to Early Cretaceous. It is possible that the TLF played a key role in lithospheric delamination and thinning and in the generation of the high-Mg adakitic rocks.